Attitudes, perceptions and AI self-efficacy in K-12 education - Nina Bergdahl; Jeanette Sjöberg (Computers and Education: Artificial Intelligence)
Access to AI-driven chatbots is triggering schools to transform. Easy access and questions of cheating are balanced against potential upsides of individual support, time savings, and the risk of falling behind. Therefore, insights into teachers’ AI self-efficacy and attitudes towards the integration of AI-driven chatbots in education necessitate research. This study approaches teachers' readiness to use AI-driven chatbots. A survey and poll questions were administered, yielding 312 and 406 responses respectively, focusing on AI self-efficacy, attitudes, and perceived usefulness in education. Preliminary findings show that while teachers are generally positive about the potential of AI in education, their AI self-efficacy varies significantly based on prior use of the technology, perceived relevance, and the support available to them. The study highlights the need for internal support and targeted professional development interventions and offers practical insights for policymakers, educators, and curriculum developers to foster teacher readiness and competence in using AI-driven chatbots in their professional tasks, in and outside of class.